PENGEMBANGAN MEDIA KOMIK FABEL “KELINCI DAN KURA-KURA” PADA MATERI TOKOH DAN WATAK KELAS II SEKOLAH DASAR - Lutfiatul Aminin; Kukuh Andri Aka; Bagus Amirul Mukmin (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the validity, practicality, and effectiveness of the "Rabbit and Tortoise" fable comic media regarding the topic of characters and character traits for second-grade elementary school students. The research employs the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. Research instruments included validation sheets for media and subject matter experts, teacher and student response questionnaires, and a learning outcome test (post-test). The results indicate that: (1) the media's validity achieved an average score of 88% (categorized as “very valid”), comprising 92% from the media expert and 84% from the subject matter expert; (2) the media's practicality achieved a score of 98.75% in the limited trial, while the extensive trial yielded teacher and student response scores of 98% and 95% respectively (averaging 96.5%), placing it in the “very practical” category; and (3) the media's effectiveness was demonstrated by a classical learning mastery rate of 100% in the limited trial and 95% in the extensive trial, classifying it as "effective.” Thus, the “Rabbit and Tortoise” fable comic media is deemed very valid, very practical, and effective, making it suitable for use in Indonesian language instruction regarding characters and character traits for second-grade elementary school students.